A closer look at the loam stucco ceiling of Rapenburg 65 in Leiden (Bulletin KNOB, 2007)
A recent restoration presented the opportunity for further research into the loam stucco ceiling of Rapenburg 65. In all probability this ceiling was realized by stucco worker Craeckenborch directly after 1623, when Matthias van Overbeke bought the building and had it almost completely rebuilt. The affinity this ceiling demonstrates with East-Netherlands and German ceilings is to be explained by the Cologne background of Van Overbeke.The ceiling appears to be an inextricable part of the construction of the building. The construction consists of pinewood joisting of secondary and tertiary beams and a roof construction with stacked trusses (with contemporary use of oak and lime wood).Between the tertiary beams small shelves have ingeniously been put in, to which the loam stucco was applied. The support of loam stucco is finished with a stucco layer on which a completely white geometric ceiling was created by means of profiled moulding and prefabricated ornaments.